2016
DOI: 10.1007/s00330-016-4291-9
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous trans-hepatic portal and hepatic vein embolization before major hepatectomy: the liver venous deprivation technique

Abstract: • Twenty-three days after LVD, FRL increased from 28.2 % (range:22.4-33.3 %) to 40.9 % (range:33.6-59.3 %) • During the first 7 days, venous-deprived liver volume increased (+13.4 %) • Venous-deprived liver volume strongly decreased (mean atrophy:229 cc; -21.3 %) at 3-4 weeks • Histology of venous-deprived liver revealed sinusoidal dilatation, hepatocyte necrosis and important atrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
180
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(188 citation statements)
references
References 31 publications
6
180
1
1
Order By: Relevance
“…32 53,54 Finally, sequential ipsilateral hepatic vein embolization after PVE has been reported to result in a greater FLR increase compared with PVE alone. [55][56][57][58][59] According to the largest series including 12 patients, the mean proportion of FLR/total liver volume was 39.7% ± 0.6% 1 to 2 weeks after PVE, and 44.2% ± 1.1% 2 weeks after hepatic vein embolization.…”
Section: Technical Refinements For Increasing Flrmentioning
confidence: 99%
“…32 53,54 Finally, sequential ipsilateral hepatic vein embolization after PVE has been reported to result in a greater FLR increase compared with PVE alone. [55][56][57][58][59] According to the largest series including 12 patients, the mean proportion of FLR/total liver volume was 39.7% ± 0.6% 1 to 2 weeks after PVE, and 44.2% ± 1.1% 2 weeks after hepatic vein embolization.…”
Section: Technical Refinements For Increasing Flrmentioning
confidence: 99%
“…The technique involves RPVE and embolization of the right and/or middle hepatic vein during the same procedure. An initial pilot study involving 7 patients by Guiu et al [44 ]reported an FLR increase from 28.2% (range 22.4-33.3%) to 40.9% (range 33.6-59.3%) at 23 days following LVD. In a follow-up study of 10 patients, FLR volume increased by 53.4% as early as 7 days following LVD.…”
Section: Options To Improve Future Liver Remnant Hypertrophymentioning
confidence: 99%
“…2 patients experienced interval disease progression, and 1 patient had insufficient FLR hypertrophy. No patients who underwent surgery developed postoperative liver failure [44,45,46]. While these early results with LVD are encouraging, comparison studies are necessary to evaluate the additional benefit provided by simultaneous PVE and HVE.…”
Section: Options To Improve Future Liver Remnant Hypertrophymentioning
confidence: 99%
“…The potential benefit of LVD as compared to PVE is more massive and rapid hypertrophy, similar to ALPPS. Guiu et al 5 reported on a series of 7 patients who underwent LVD, with technical success achieved in all patients. FLR was reported to increase from 28.2% (22.4%–33.3%) to 40.9% (33.6%–59.3%%) over a 23-day period.…”
Section: Techniques For Liver Regenerationmentioning
confidence: 99%